Ghostbusters (2016) [videorecording (DVD)] - Feig, Paul; McCarthy, Melissa, 1969-; Wiig, Kristen, 1973-; McKinnon, Kate, 1984-; Jones, Leslie, 1967-; Hemsworth, Chris (Sony Pictures Home Entertainment, 2016)
Following a ghost invasion of Manhattan, paranormal enthusiasts Erin Gilbert and Abby Yates, nuclear engineer Jillian Holtzmann, and subway worker Patty Tolan band together to stop the otherworldly threat.